Rethinking the Polemical Studies on Abu Hurayrah’s Transmitted Hadiths - Abolaji Abdrahman Ismail (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
After the Holy Quran, as the first book containing divine information, the Hadith is also the second sacred book. Abu Hurayrah was one of the most famous transmitters of the large Hadiths and has also attracted some criticism, leading to polemical studies on his transmitted Hadiths. Thus, this study aims to offer new insights into these seminal works. Furthermore, this study aims to rethink the critiques against Abu Hurayrah. The method of this study is qualitative, and the approach is argumentative and analytic. It relies on content analysis and analogical deduction. The results of the study show demonstrates that Abu Hurayrah really transmitted the large Hadiths due to his ascetic lifestyle. It shows that Abu Hurayrah transmitted nine Hadiths every day for the period of a year and nine months. It also proves that Abu Hurayrah and the other companions like him transmitted large Hadith without having a close relationship to the Prophet.